Cost-Effectiveness Analysis of Percutaneous Vertebroplasty for Osteoporotic Compression Fractures. Issue 3 (April 2017) - Takura, Tomoyuki; Yoshimatsu, Misako; Sugimori, Hiroki; Takizawa, Kenji; Furumatsu, Yoshiyuki; Ikeda, Hirotaka; Kato, Hiroshi; Ogawa, Yukihisa; Hamaguchi, Shingo; Fujikawa, Atsuko; Satoh, Toshihiko; Nakajima, Yasuo
Abstract : Study Design: Single-center, single-arm, prospective time-series study. Objective: To assess the cost-effectiveness and improvement in quality of life (QOL) of percutaneous vertebroplasty (PVP). Summary of Background Data: PVP is known to relieve back pain and increase QOL for osteoporotic compression fractures. However, the economic value of PVP has never been evaluated in Japan where universal health care system is adopted. Methods: We prospectively followed up 163 patients with acute vertebral osteoporotic compression fractures, 44 males aged 76.4±6.0 years and 119 females aged 76.8±7.1 years, who underwent PVP. To measure health-related QOL and pain during 52 weeks observation, we used the European Quality of Life–5 Dimensions (EQ-5D), the Rolland-Morris Disability Questionnaire (RMD), the 8-item Short-Form health survey (SF-8), and visual analogue scale (VAS). Quality-adjusted life years (QALY) were calculated using the change of health utility of EQ-5D. The direct medical cost was calculated by accounting system of the hospital and Japanese health insurance system. Cost-effectiveness was analyzed using incremental cost-effectiveness ratio (ICER): Δ medical cost/Δ QALY. Results: After PVP, improvement in EQ-5D, RMD, SF-8, and VAS scores were observed. The gain of QALY until 52 weeks was 0.162. The estimated lifetime gain of QALY reached 1.421. The direct medical cost for PVP was ¥286, 740 (about 3061 US dollars). Cost-effectiveness analysis using ICER showed that lifetime medical cost for a gain of 1 QALY was ¥201, 748 (about 2154 US dollars). Correlations between changes in EQ-5D scores and other parameters such as RMD, SF-8, and VAS were observed during most of the study period, which might support the reliability and applicability to measure health utilities by EQ-5D for osteoporotic compression fractures in Japan as well. Conclusions: PVP may improve QOL and ameliorate pain for acute osteoporotic compression fractures and be cost-effective in Japan.